Clustering Technique for Constructing Path Loss Model in Bangkok Metropolis - Chomsuay, Danupol; Phakphisut, Watid; Wijitpornchai, Thongchai; Areeprayoonkij, Poonlarp; Jaruvitayakovit, Tanun (My University, 2022)
This paper presents the path loss model for any areas of Bangkok metropolis. In general, the path loss models can be divided into three main categories: rural, suburban, and urban. However, in this work, we propose the clustering technique which can divide Bangkok metropolis into many areas. Then, the path loss model is designed according to the characteristics of each area. We use the standard propagation model (SPM) to design the path loss. We also use the least square method for finding the optimal parameter of SPM. The results show that our BK900 model, BK1800 model, and BK2100 model can provide the RMSE around 2.9 dB, 3.2 dB, and 4.8 dB, respectively.
Keywords: Clustering Technique; Path Loss Model; Standard Propagation Model